HUBUNGAN KARKTERISTIK PEKERJA DAN BEBAN KERJA FISIK DENGAN KELUHAN MUSKULOSKELETAL PADA PEKERJA INDUSTRI PENGOLAHAN SUSU DI BOYOLALI - Hapsari, Mia Nur; Qadrijati, Isna; Haryati, Sri (Jurnal Kesehatan Masyarakat, 2023)
Musculoskeletal Disorders has became the most work-related injuries in the world. Besides, musculoskeletal Disorders is dangerous enough because it could raise chronic pain and decreased someone’s life quality. Musculoskeletal disorders caused by many of factors there are individual characters and physical work-load. This research aim to determine the correlation between workers characters (age, gender, body mass index, work period) and physical work-load to musculoskeletal disorders among to PT So Good Food Unit-UHT packing workers. This type of research used analytical obervational designed with cross sectional. The parameter observed was  Musculosceletal Disorders measured with Nordic Body Map Questionaire. The respondents of this research were the packing workers in PT So Good Food Unit-UHT Boyolali with the number 96 out of 121 workers. The sampling technique used Simple Random Sampling. Based on Pearson test showed there was correlation between age and musculoskeletal disorders (p value = 0.000), there was correation between body mass index with musculoskeletal disorders (p value = 0.001), and there was correlation between physical work-load and musculoskeletal disorders (P value = 0.000). The Eta correlation shown that there was correlation between gender and musculoskeletal disorders (p value = 0.005). From this research, it can be concluded that there are significant correlation between worker’s characteristics and physical work-load to musculoskeletal disorders. Researchers suggest that the further researches are needed to research the others factors related to Musculoskeletal Disorders excluded this research.